The strategy of integrating tolerance values into civics learning in inclusive school - Dwintari, Julita Widya; Murdiono, Mukhamad (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Tolerance is one of the essential characters to be instilled in a plural society. This study aims to determine the strategy for integrating the value of tolerance into civics learning in inclusive education schools. This research is qualitative descriptive research with interview data collection techniques, observation, and document analysis. The strategy for integrating the value of tolerance in civics learning in inclusive education-provided schools is carried out through the stages of planning, implementing, and evaluating learning. They were designing learning plans for regular and inclusive students and improving teaching competencies in inclusive classes. Implementation of learning is done by providing advice and motivation during learning, taking a dynamic approach with students, forming an attitude of empathy, appreciating the tolerant attitude shown by students, and applying a heterogeneous group learning model. The assessment is carried out by distinguishing the assessment content between students who do not have special needs and students with special needs that are adjusted to their obstacles and abilities.